Phosphorylation of Radix Cyathula officinalis polysaccharide improves its immune-enhancing activity. Issue 1 (2nd January 2020) - Lin, Lang; Yang, Jie; Yang, Yan; Zhi, Hui; Hu, Xin; Chai, Dongkun; Liu, Yunjie; Shen, Xiaojun; Wang, Jie; Song, Yunqi; Zeng, Aimei; Li, Xinyu; et al.
Abstract: In this study, the effects of phosphorylation of Radix Cyathula officinalis polysaccharide (RCPS) on its immunological properties were evaluated using broiler chickens immunized with Newcastle disease vaccine (NDV). The results suggested that phosphorylated RCPS (pRCPS) could enhance antibody titers against NDV vaccination, improve the indexes of thymus, the bursa of fabricius and spleen, and up-regulate IL-2, IL-4, IL-5, IL-6, IL-10, and IFN-γ. Overall, pRCPS could significantly improve cellular and humoral immune responses in broiler chickens immunized with NDV and thus represents a useful immunotherapeutic agent. Graphical Abstract: